Dampak Tunggakan Pembayaran Rekening Air oleh Pelanggan terhadap Penerimaan Kas PT ABC - Raka Irfansyah; Fajar Syaiful Akbar (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the impact of customer water bill payment arrears on the cash receipts of PT ABC. The research method used is a descriptive method with a qualitative approach through interviews, observations, and document analysis. The results of the study show that water bill payment arrears have various negative impacts on the company’s financial condition. These conditions hinder the company in meeting its short-term obligations and disrupt long-term financial planning. Therefore, effective receivables management and the implementation of a more efficient billing system are essential to maintain the stability of PT ABC’s cash receipts.